[my-mała grecka litera m]-Analysis and robust stability of positive linear systems - Hinrichsen, Diederich; Son, Nguyen K. (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, we develop a ?-analysis for nonnegative matrices and apply the results to analyse robust stability of positive linear continuous-time systems under arbitrary affine parameter perturbations. It is shown that real and complex stability radii of positive systems coincide for arbitrary affine perturbation structures, in particular for block-diagonal disturbances. Estimates and computable formulae are derived for these stability radii.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka